2009
DOI: 10.4103/0022-3859.58940
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram-like reaction with ornidazole

Abstract: Many drugs are implicated in causation of disulfiram-like reaction. The disulfiram-like reaction can vary in severity and can occasionally be fatal. The reaction is believed to result from inhibition of metabolism of acetaldehyde to acetate by inhibition of aldehyde dehydrogenase. The increase in serum acetaldehyde results in unpleasant clinical manifestations. Metronidazole is known to cause disulfiram-like reaction. Although no previous report has implicated ornidazole in causation of disulfiram-like reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Such an increase in the conductivity may be explained on the basis of the fact that ion implantation in polymers, leads to the formation of free radicals & dangling bonds, release of low molecular weight volatile species like hydrogen, trapping of high molecular weight fragments, etc leading to the creation of carbonaceous clusters on the implanted surface which are rich in charge carriers [6][7] which provide the continuous path for the charge transfer within the insulating polymer chain. The creation of such carbonaceous clusters on the implanted surface has been confirmed through Raman spectroscopy ( Figure 2) which revealed that all characteristic peaks of virgin PC have disappeared with the appearance of a band at wavenumber ~1530 cm -1 corresponding to the characteristic Gbands of hydrogenated amorphous carbon [6][7].…”
Section: Resultsmentioning
confidence: 99%
“…Such an increase in the conductivity may be explained on the basis of the fact that ion implantation in polymers, leads to the formation of free radicals & dangling bonds, release of low molecular weight volatile species like hydrogen, trapping of high molecular weight fragments, etc leading to the creation of carbonaceous clusters on the implanted surface which are rich in charge carriers [6][7] which provide the continuous path for the charge transfer within the insulating polymer chain. The creation of such carbonaceous clusters on the implanted surface has been confirmed through Raman spectroscopy ( Figure 2) which revealed that all characteristic peaks of virgin PC have disappeared with the appearance of a band at wavenumber ~1530 cm -1 corresponding to the characteristic Gbands of hydrogenated amorphous carbon [6][7].…”
Section: Resultsmentioning
confidence: 99%
“…But the reaction occasionally could be severe enough to cause death. [1] Some cephalosporin could cause disulfiram-like reaction. Among these cephalosporins, the reaction is most often seen in cefoperazone, cefotetan, and moxalactam.…”
Section: Introductionmentioning
confidence: 99%
“…A death due to an ethanol/ metronidazole interaction [42] and features of disulfiram-like reactions with ornidazole [43] have been reported. And despite the considerable number of case reports describing the association with disulfiram-like reactions secondary to metronidazole and ethanol interaction, reactions do not occur in all patients, suggesting an individual susceptibility [44].…”
Section: Disulfiram-like Reactions With Anti-infective Drugsmentioning
confidence: 99%
“…Besides, the mechanism by which metronidazol induces intolerance to alcohol remains unclear [45]. However, clear advice to abstain from alcohol is warranted when metronidazole or its congeners are prescribed [43].…”
Section: Disulfiram-like Reactions With Anti-infective Drugsmentioning
confidence: 99%
See 1 more Smart Citation